Hypermethylation of the 16q23.1 Tumor Suppressor Gene ADAMTS18 in Clear Cell Renal Cell Carcinoma - Xu, Ben (Int J Mol Sci, 2015)
To identify tumor suppressor genes (TSGs) silenced by hypermethylation and discover new epigenetic biomarkers for early cancer detection. ADAMTS18, located at 16q23.1, has been reported to be a critical TSG in multiple primary tumors; however, this has not yet been verified in clear cell renal cell carcinoma (ccRCC). We explored epigenetic alterations in this gene in ccRCC and analyzed possible clinicopathological associations. We examined ADAMTS18 gene expression and methylation by semi-quantitative reverse transcription PCR (RT-PCR) and methylation-specific polymerase chain reaction (MSP) in 5 ccRCC-derived cell lines before and after treatment with 5-aza-2'-deoxycytidine (5-AzaC). MSP was further performed for 101 ccRCC primary tumors and 20 adjacent normal tissues. Some cell lines and specimens were examined by subsequent bisulfite genomic sequencing (BGS) and real-time PCR. Further, we analyzed the relationship between the ADAMTS18 gene methylation and clinicopathological features, including short-term disease-free survival (DFS), in patients with ccRCC. ADAMTS18 down-regulation and hypermethylation were detected in the ccRCC-derived cell lines using RT-PCR and MSP. Treatment with 5-AzaC reversed the hypermethylation of the ADAMTS18 gene and restored its expression. Hypermethylation was further detected in 44 of 101 (43.6%) primary tumors and 3 of 20 (15.0%) adjacent normal tissues. However, a significant difference between both groups was observed (p = 0.02). BGS analysis and real-time PCR were subsequently performed to confirm the results of RT-PCR and MSP. Furthermore, the methylation status of ADAMTS18 was not significantly associated with gender, age, location, tumor diameter, pathological stage, nuclear grade or short-term DFS in patients with ccRCC (p > 0.05). The ADAMTS18 gene is often down-regulated by hypermethylation in ccRCC-derived cell lines and primary tumors, indicating its critical role as a TSG in ccRCC. We conclude that ADAMTS18 gene hypermethylation may be involved in the tumorigenesis of ccRCC and may serve as a novel biomarker for this disease.